Criança, educação, cultura e linguagem: ações de leitura e escrita nos anos iniciais do ensino fundamental - OLIVEIRA, Ediuma Cordeiro de (2023)
This article discusses the experiences of an extension project developed in the area of ​​education by the Federal University of Pará, on the Campus of Abaetetuba. Its objective was to discuss the importance of promoting pedagogical actions in favoring the teaching and learning process, starting from the study of extension activities of the pedagogical plan in the field of reading and writing of children in the early years of elementary school in a rural school. in the city of Irituia/PA. Freire (2006), Vigotsky (19980 and Kramer 92007) were used to support the theme. Methodologically, this work presents itself as a study with a qualitative approach supported by the Final Report of the extension project on the pedagogical work in the field, in addition to observations and descriptions during the extension activities carried out. As a result, the scientific contribution to area studies stands out, as well as learning about the processes of establishing activities on literacy and literacy, as well as didactic, cultural and recreational actions.